Gamification on social media : a study on Duolingo's use of gamification on Instagram - Hoek, Felicia van (2021)
Over the years, social media has been growing and changing exponentially. With that comes the importance of social media marketing and the need for user interaction and engagement. To keep up with the changes, marketeers are forced to continuously keep adapting their (digital-) marketing strategies as well as their overall marketing efforts. Research suggests that gamification can be used as a useful tool to add- and build sustained value through interpersonal interactions. Existing research shows a limitation when it comes to linking gamification to theoretical principles, the connection is thin, and the empirical research is scarce. The existing studies have mainly been founded on similar, often motivation-related theories – with in particular the Self-Determination Theory, with some studies lacking a theoretical foundation entirely. Additionally, limitations were recognised in the existing research merely investigating the connection between few gamification mechanics and/or brandrelated aspects, only covering a few aspects of gamification. Therefore, this thesis aims to contribute to the existing research by analysing how Duolingo, a language learning platform, uses different gamification elements in their social media. A qualitative content analysis is conducted with the data consisting of 353 Instagram posts from Duolingo, published between October 2012 and January 2021. The findings show the utilisation of multiple, frequently used gamification elements across different social media post types, as well as close relations between different gamification dimensions, i.e. the five different groups Performance/measurement, Ecological, Social, Personal, and Fictional, with each of these group including a number of different gamification elements, such as Acknowledgement, Chance, and Competition, among others.